THE EFFECT OF DIFFERENT LEVELS OF VITAMIN E ON THE REPRODUCTIVE PERFORMANCE OF ZEBRAFISH (Danio rerio) - N.B.P Utomo; M. Zairin Junior; T.L. Yusuf; I. Mokoginta; M. Bintang (Jurnal Akuakultur Indonesia)
This experiment was conducted to determine the dietary Vitamin E requirement for reproduction of broodstock zebrafish Danio rerio.  Four isonitrogenous (39% crude protein) and isocaloric (3,260 kcal digestible energy/kg diet) practical diets, namely diets A, B, C, and D with different levels of Vitamin E were fed to zebrafish broodstock.  The broodstock were cultivated in aquaria.  Diet A contained low dosage of Vitamin E (5 mg Vitamin E /kg diet), while diets B (62 mg Vitamin E /kg diet), C (125 mg Vitamin E /kg diet), and diet D (187 mg Vitamin E /kg diet), combined respectively with 1% n-3 fatty acids and 2% n-6 fatty acids.  Fish were fed ad satiation for 60 days using these diets.  During feeding period, gonad maturation stages were examined.  The dietary with different level of Vitamin E affected egg size, chemical content, total number of larvae, normal larvae, and survival rate of larvae produced, fecundity, fertilization rate, and hatching rate.  On the other hand, fish fed on experimental diets did not show any significance differences in the gonad somatic index, fecundity, fertilization rate, and hatching rate.  Fish fed on diet D produced the highest fecundity (633.65 ± 71.86 eggs/grams of fish), fertilization rate (92.3 ± 7.7%), and hatching rate (80.31 ± 9.8%).  The total lipid content of eggs were significant, ranging from D (39.7%), C (33.5%), B (32.1%), and A (29.5%).  At a dosage of 1% of dietary n-3 fatty acids and 2% n-6 fatty acids, zebrafish require 187 mg Vitamin E/kg feed in the diet for reproduction.  .